Integrating value of research into NCI Clinical Trials Cooperative Group research review and prioritization: A pilot study. (20th July 2018) - Carlson, Josh J.; Kim, David D.; Guzauskas, Gregory F.; Bennette, Caroline S.; Veenstra, David L.; Basu, Anirban; Hendrix, Nathaniel; Hershman, Dawn L.; Baker, Laurence; Ramsey, Scott D.
Abstract: Background: The Institute of Medicine has called for approaches to help maximize the return on investments (ROI) in cancer clinical trials. Value of Research (VOR) is a health economics technique that estimates ROI and can inform research prioritization. Our objective was to evaluate the impact of using VOR analyses on the clinical trial proposal review process within the SWOG cancer clinical trials consortium. Methods: We used a previously developed minimal modeling approach to calculate VOR estimates for 9 phase II/III SWOG proposals between February 2015 and December 2016. Estimates were presented to executive committee (EC) members (N = 12) who determine which studies are sent to the National Cancer Institute for funding consideration. EC members scored proposals from 1 (best) to 5 based on scientific merit and potential impact before and after receiving VOR estimates. EC members were surveyed to assess research priorities, proposal evaluation process satisfaction, and the VOR process. Results: Value of Research estimates ranged from −2.1B to 16.46B per proposal. Following review of VOR results, the EC changed their score for eight of nine proposals. Proposal rankings were different in pre‐ vs postscores ( P value: 0.03). Respondents had mixed views of the ultimate utility of VOR for their decisions with most supporting (42%) or neutral (41%) to the idea of adding VOR to the evaluation process. Conclusions: The findings from this pilot study indicate use of VOR analyses may be a useful adjunct to inform proposal reviews within NCI Cooperative Clinical Trials groups. Abstract : The Instiztute of Medicine has called for approaches to help maximize the return on investments in cancer clinical trials. The findings from this pilot study indicate use of value of research analyses may be a useful adjunct to inform proposal reviews within NCI Cooperative Clinical Trials groups.